Cloning gene fragment containing sequences of B gene activates anthocyanin biosynthesis in local sticky corn cultivars (Zea mays subsp. ceratina (Kuelshov) Zhuk) - Nhàn, Phạm Thị Thanh; Đức, Lê Hoàng; Ngà, Nguyễn Thị Thu; Bình, Lê Trần (Vietnam Journal of Biotechnology, 2016)
Sticky corn (Zea mays subsp. ceratina (Kuelshov) Zhuk) is one of the widely grown plants in Vietnam, especially in mountainous regions. The local cultivars play an important role for people living in regions with water limitation and mountain slopes. Anthocyanin is considered a sign of the stress caused by drought. The expression of the structural genes and enzymes involved in anthocyanin biosynthesis in parts of maize require the presence of transcription factors belonging to MYB, Myc (or bHLH) and WD40. Genes of the MYB family regulating anthocyanin biosynthesis have been studied including C1 (Colored Aleurone 1), P1 (Purple), Pl (Purple leaf). Similarly, genes of Myc family (or bHLH) have been studied including B, R, Sn and Lc (Leaf color). Locus B (or b1) consist of alleles B- I, B- Peru, B-Bolivia. These proteins activate structural genes CHS, CHI, F3H, DFR, ANS, Bz, in which CHS, DFR and F3H are key genes of the anthocyanin biosynthesis. This paper analyzed the sequence of a segment of B gene that activates anthocyanin biosynthesis. We have cloned and determined the sequence of a part of genes B from NH and BS1 maize cultivars. The sequence consists of 801 nucleotides encoding 267 amino acids. The deduced protein of segments of gene B has 9 amino acid position changes among NH, BS1 and b1 gene on GenBank. The sequence of a segment of B gene in NH and BS1 had high similarity with genes b1, B1 and B- Peru (98.8%, 99.1% and 98.8%)